Defining Experiential Education: Students describe what gives learning its high impact. - Cicchino, Amy; Alvarez, America; Chandrakumar, Villiei; Miramontes, Isaiah; Sisson, Abby; Smith, Glenn; Underwood, Greg (Experiential Learning and Teaching in Higher Education, 2024)
ELTHE invited six students from around the country to talk with editor Amy Cicchino about their most powerful educational experiences, and the role of hands-on learning in their college careers. The conversation follows a similar roundtable discussion in our last issue, among seminal thinkers in the field. Like that article, this one has been edited and condensed.